A new species of Homalota Mannerheim, 1830 (Coleoptera: Staphylinidae: Aleocharinae) from Nanjing, China - Cao, Dandan; Wei, Jianrong; Liu, Shuwen; Zhao, Zhengping; Wang, Liping; Ji, Baozhong (Zootaxa, 2018)
A new species, Homalota nanjingensis Cao, Ji & Liu, sp. nov. from Jiangsu province of China, is described and illustrated. Photographs of the body and mouthparts, line drawings of the aedeagus and spermatheca are provided.